If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + -4(x + -3) = 33 Reorder the terms: 7x + -4(-3 + x) = 33 7x + (-3 * -4 + x * -4) = 33 7x + (12 + -4x) = 33 Reorder the terms: 12 + 7x + -4x = 33 Combine like terms: 7x + -4x = 3x 12 + 3x = 33 Solving 12 + 3x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 3x = 33 + -12 Combine like terms: 12 + -12 = 0 0 + 3x = 33 + -12 3x = 33 + -12 Combine like terms: 33 + -12 = 21 3x = 21 Divide each side by '3'. x = 7 Simplifying x = 7
| t/250=150/375 | | 1/4(2x+5)=x-2/5 | | =(7x+9y-2x)(8x-3x-3y) | | 7x+1=2x+6 | | 1/2+(0.7)2 | | (3x+2)=(x-7) | | -9x+63=135 | | (m^-1m5/m^-2)^-3 | | -1/12x+8=7/6 | | x/0.02=32.8 | | -3x=18.9 | | 4c-6=250 | | 47y+5x=360 | | 3x-10=12x | | x(3x^2+5x-4)-3(3x^2-x)=0 | | X*X-3=-2 | | 7(r+3)= | | 2x+7y=28 | | 8p+4-8p= | | x*.06=3500 | | 6x-73+8x+43=180 | | 5t+36=-249 | | x/-8=-5 | | -4m+5.5=16 | | x/7-56=-54 | | y2=25/49 | | 4x-37=-13 | | 2x+114+8x+72=180 | | 6x+8=-33-8x | | 4x+3=-8x-21 | | (X+3)(x-2)=4(x+1) | | 3(9x+6)=27x-5 |